2002
DOI: 10.1103/physrevlett.89.136101
|View full text |Cite
|
Sign up to set email alerts
|

Nanostressors and the Nanomechanical Response of a Thin Silicon Film on an Insulator

Abstract: Pseudomorphic three-dimensional Ge nanocrystals (quantum dots) grown on thin silicon-on-insulator substrates can induce significant bending of the silicon template layer that is local on the nanometer scale. We use molecular dynamics simulations and analytical models to confirm the local bending of the Si template and to show that its magnitude approaches the maximum value for a freestanding membrane. The requisite greatly enhanced viscous flow of SiO2 underneath the Si layer is consistent with the dependence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
52
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 17 publications
3
52
0
2
Order By: Relevance
“…2͑f͔͒. Therefore, it provides an indirect support to the suggestion that the experimentally observed large local bending 6,7 is assisted by the local nonlinear viscous flow of SiO 2 , because no void was observed in the experiment. 6,7 A direct proof, however, requires simulation of the nonlinear viscoelastic property of SiO 2 .…”
supporting
confidence: 57%
See 2 more Smart Citations
“…2͑f͔͒. Therefore, it provides an indirect support to the suggestion that the experimentally observed large local bending 6,7 is assisted by the local nonlinear viscous flow of SiO 2 , because no void was observed in the experiment. 6,7 A direct proof, however, requires simulation of the nonlinear viscoelastic property of SiO 2 .…”
supporting
confidence: 57%
“…6 Our theory further showed that the magnitude of the observed local bending approaches the linear elastic limit for a freestanding Si layer, and such bending instability may occur generally for a very thin freestanding Si layer when the Ge island density is low. 7 Because experimentally no vacuum blister ͑void͒ was observed at the Si/ SiO 2 interface, it is suggested that the local bending of Si is achieved by a local nonlinear viscous flow of SiO 2 which makes Si layer behave like a freestanding film. 6,7 In this letter, using finite element analysis ͑FEA͒, we examine the mechanical stability of ultrathin Ge/ Si/ SiO 2 composite film within the linear elastic regime, without viscous flow of SiO 2 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4, 1 2 h s / R is estimated using Ref. 9 and compared to the strain predicted by elastic strain sharing. 1 For all template layer thicknesses greater than 2.4 nm, the predicted strain at the template layer-hut interface due to curvature exceeds the strain developed by elastic strain sharing, reaching a maximum of 1.6% on 4-nm-thick template layers.…”
Section: -mentioning
confidence: 99%
“…With appropriate growth conditions, even SOI template layers constrained by the buried oxide layer can be distorted by Ge huts. 8,9 In this letter, we present a conceptually simpler approach: to fabricate Ge huts on freestanding template layers. These layers can be deformed without requiring the unusually high growth temperatures of 700°C that must be used to cause SiO 2 to flow beneath unreleased layers.…”
mentioning
confidence: 99%